Prospective general health assessment in cardiac surgery patients with postoperative delirium: a questionnaire-based study - Krzych, Łukasz; Woźnica, Anna; Wilczyński, Mirosław; Białek, Krzysztof; Krupka-Matuszczyk, Irena; Bochenek, Andrzej (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Background : Delirium is a serious complication which occurs postoperatively in up to half of all cardiac surgery patients. An increased risk of death, wound infection, respiratory insufficiency and prolonged hospital stay are found to be related to delirium incidence. Aim : We attempted to assess health condition and its determinants in patients with postoperative delirium using a questionnaire method. Material and methods : In a prospective manner (5-y follow-up, median 2.3) we investigated general health condition in 201 patients (74.1% males, 25.9% females) aged 40-90 years (mean 71.4) who fulfilled the GHQ-28. Health condition was assessed in points within 4 sub-scales (somatic condition, fear, social disability, depressive symptoms). The total number of points was used to describe the overall health condition. Results : The occurrence of delirium was 6.1%. The total number of points in a questionnaire was 26.4 ±15.5. The main problem in the investigated patients was social disability (9.37 ±4.1 points) and somatic condition (9.68 ±4.6 pts). Fewer problems were related to fear (6.96 ±4.8 pts) and depression (3.43 ±4.4 pts). All GHQ features were more pronounced in women (p < 0.05). The general good health condition was found in 34.1%, moderate in 43.5% and unsatisfactory in 22.4% of the patients. Diabetics, patients with perioperative atrial fibrillation or postoperative stroke/TIA, those with a history of peripheral artery disease and persons undergoing valve surgery had statistically significantly worse general health condition (p < 0.05 for all). Conclusions: Delirium decreases general health condition in cardiac surgery patients in a follow-up. Health condition is influenced by several co-morbidities. Because general health condition is the acknowledged measure of patients’ satisfaction, there is a strong need to implement preventive actions with subsequent assessment of their usefulness in cardiac surgery.